Deep Ecology: A Concept towards Nature Preservation in the Short Stories of Ruskin Bond: Exploring the Deep Ecology in Ruskin Bond's Short Stories (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Ruskin Bond is always concerned about nature and its smallest creatures. His minute description about nature always depicts the multifaceted hazards done to nature due to the greed of humanity. He breathes the fresh rejuvenating air of Himalayas to whom he is pledged to defend and protect. Every single piece of writing composed by him reflects his deep love and consideration for Mother Nature. Hardly are there such writers who go so much deep in their dealing of ecology and presents the description of rare species and insects. He values every smallest insect and moth in the great plan of God. Nothing escapes from the microscopic eyes of Bond. The spectacular Himalayas haunted him in England and he rushed back to them to drink the sweet water from lonely rivulets, to roam in the pastures green, to sit amid grooves and to smell the revitalizing fragrance of flowers. Trees and plants are not the background in his stories but the characters itself.